ABCDE PROTOCOL: IMPORTANCE OF THE SYSTEMATIC APPROACH AND INITIAL DIAGNOSTIC SUPPORT (CIPEEX, 2025)
INTRODUCTION: The ABCDE approach (Airway, Breathing, Circulation, Disability, Exposure) is recommended in emergency situations for the initial stabilization of critically ill patients. Its correct application, combined with complementary tests, enables early diagnosis, rapid intervention, and reduced mortality. However, studies show low practical adherence, highlighting a gap between theory and clinical application. OBJECTIVE: To assess the level of knowledge, adherence, and factors influencing the application of the protocol, as well as its integration with complementary exams. METHODOLOGY: This is a descriptive study. The research was conducted using electronic databases—PubMed, Scielo, ScienceDirect, and BMC Journals—employing the descriptors “ABCDE approach,” “initial assessment,” and “emergency care.” Original studies of the observational, cross-sectional, and simulated clinical trial types, published between 2017 and 2025, were included. Extracted data comprised: study type, evaluated sample, context, adherence rate to the protocol, main findings, and factors impacting practical application. RESULTS: Practical adherence to the protocol proved limited. In the clinical trial with 72 neonatal professionals, only 31.5% correctly followed the ABCDE sequence, with better performance in the video-trained group (38.8% vs. 27.8%)¹. Regarding application in unstable patients, adherence occurred in only 33% of cases². Concerning theoretical knowledge, studies with 240 professionals showed an average accuracy rate of 80.1%³, whereas among interns and residents it was 59.1%⁴. Barriers such as lack of formal training, absence of institutional protocols, and limited technical knowledge compromised proper execution. Laboratory tests (blood gas analysis, complete blood count) and imaging (FAST, chest X-ray) proved essential in stages B, C, and E⁵. CONCLUSION: Despite the proven effectiveness of the ABCDE protocol, its practical application remains unsatisfactory, requiring reinforcement in education, the use of clinical simulations, educational videos, and institutional support. The early integration of complementary tests is crucial for rapid and effective decision-making in emergency settings.